2017
DOI: 10.1155/2017/6405278
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diet and Nutritional Supplements in Parkinson’s Disease Progression

Abstract: Objectives The goal of this study is to describe modifiable lifestyle variables associated with reduced rate of Parkinson's disease (PD) progression. Methods The patient-reported outcomes in PD (PRO-PD) were used as the primary outcome measure, and a food frequency questionnaire (FFQ) was used to assess dietary intake. In this cross-sectional analysis, regression analysis was performed on baseline data to identify the nutritional and pharmacological interventions associated with the rate of PD progression. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 49 publications
3
95
0
3
Order By: Relevance
“…However, l ‐dopa is associated with the development of motor fluctuations and dyskinesias, and it does not adequately control many nonmotor symptoms, which are often under‐recognized yet ultimately more disabling than motor symptoms . In this context, there is growing interest in the largely unexplored, patient‐empowering approach of diet manipulation …”
mentioning
confidence: 99%
“…However, l ‐dopa is associated with the development of motor fluctuations and dyskinesias, and it does not adequately control many nonmotor symptoms, which are often under‐recognized yet ultimately more disabling than motor symptoms . In this context, there is growing interest in the largely unexplored, patient‐empowering approach of diet manipulation …”
mentioning
confidence: 99%
“…Interestingly, it is known that foods such as fresh vegetables are associated with the reduced rate of PD progression. 3,6 Therefore, it is likely that dietary intake of GF-rich cruciferous vegetables might play a role in preventing the onset of neuropsychiatric disorders in later life. In addition, the natural antioxidants (ie, the polyphenol-rich aqueous walnut extract, an extract of Juglandis Semen and pigallocatechin gallate, a major polyphenol in green tea) could protect against MPTP-induced dopaminergic neurotoxicity in mouse striatum.…”
Section: Sfn Protected Against Mptp-induced Dopaminergic Neurotoxicitymentioning
confidence: 99%
“…Importantly, diet is an excellent first step for reducing the risk for PD . For example, a high intake of fresh vegetables, fruits, nuts and seeds, fish, olive oil, coconut oil, fresh herbs, and spices is associated with a reduced risk of PD development and slower disease progression …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using our scale, we found that people who are taking CoQ10 and fish oil are statistically progressing slower than people who are not. 18 People who are taking iron supplements are progressing faster than people who are not. I have been measuring iron levels in my patients with Parkinson's for the last couple of years now, and they are higher than I realized.…”
Section: Dr Mischleymentioning
confidence: 99%